Mass Incarceration by Design: The Impacts of Urban Renewal and Landscape Architecture's Absence on the Prison Industrial Complex and the Use of Landscape Architecture as an Antidote to Mass Incarceration - Phillips, Abigail P (2016)
The work of landscape architects has both positive and negative social impacts and landscape architects can strive to intentionally design for positive social impact. This paper utilizes mass incarceration as a lens for discussing the social impact of landscape architecture. The crossroads of mass incarceration and design offer a unique opportunity for Landscape Architects to examine the impact of many urban renewal efforts on marginalized communities, the benefits of landscape architectural involvement in prison design, and the use of design as protest against inhumane structures. This paper is separated into three sections, one detailing the history of social justice and injustice in landscape architecture, one explaining how mass incarceration developed and what landscape architects can do to respond to it and another detailing The Solitary Gardens in New Orleans, a landscape-based project that advocates against the use of solitary confinement and mass incarceration through collaborative design with incarcerated people. This research suggests that Landscape Architects can combat mass incarceration in a variety of ways: through collaboration with marginalized groups when designing urban spaces, through reformative prison landscape design, through work with ex-offenders and by lobbying against the use of inhumane designs. These findings beg further research into whether it is more appropriate for designers to lead socially progressive pursuits or respond to popular movements, what the best practices for navigating between marginalized and empowered stakeholders are, what the economic feasibility of social impact design as a profession is and how to prove the mental and physical benefits of inmates with access to green infrastructure